1986
DOI: 10.1111/j.1399-3011.1986.tb03253.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptides containing dialkylglycines

Abstract: Three novel peptide analogues containing a residue of the hindered amino acid dibenzylglycine (Dbg) were prepared. Although [Glp6, Dbg7]‐substance P‐(6–11) possessed no substance P agonist or antagonist activity, [Dbg4, Leu5]‐enkephalinamide was 8.4 times as potent as [Leu5]‐enkephalinamide in isolated tissue assays for opioid activity, and proved highly δ‐selective (300‐fold). [N,N‐Di‐allyl Tyr1, Dbg4, Leu5]‐enkephalinamide was a moderately potent opioid antagonist, but showed little μ or δ selectivity. Dbg r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This result is consistent with previous research showing that the replacement of L-Phe 4 with D-Phe 4 in Leu 5 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu 5 -enkephalin containing the hindered amino acid dibenzylglycine (Dbg) at position 4 is a potent DOPR agonist (53). Based on this information, we concluded that compound 3 contains L-Phe 4 while compound 5 contains D-Phe 4 .…”
Section: Binding Properties Of Enkephalin Derivativesmentioning
confidence: 99%
“…This result is consistent with previous research showing that the replacement of L-Phe 4 with D-Phe 4 in Leu 5 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu 5 -enkephalin containing the hindered amino acid dibenzylglycine (Dbg) at position 4 is a potent DOPR agonist (53). Based on this information, we concluded that compound 3 contains L-Phe 4 while compound 5 contains D-Phe 4 .…”
Section: Binding Properties Of Enkephalin Derivativesmentioning
confidence: 99%